Whole tumor cell vaccines engineered to secrete GM‐CSF (GVAX). Issue 1 (2nd August 2021) - Soiffer, Robert J.; Kooshesh, Kameron A.; Ho, Vincent
Abstract: Generation of immunity against cancer through vaccination has long been an elusive goal for tumor immunologists. Putative candidates for vaccination targets include oncofetal antigens, viral antigens, neoantigens, and differentiation antigens. The first attempts at cancer vaccination used injections of whole autologous tumor cells. However, these unmodified tumor cells did not engender a robust immune response. Subsequent efforts were focused at enhancing the immunogenicity of whole autologous tumor cell vaccines through genetic modification, often through virally mediated transduction of genes encoding immunostimulatory molecules. Of many immunostimulatory cytokines evaluated in the context of gene‐modified tumor cell vaccines, granulocyte–macrophage colony‐stimulating factor (GM‐CSF) emerged as the most potent in generating protective antitumor immunity. Vaccination using irradiated, GM‐CSF producing tumor cells (GVAX) consistently induced antitumor immunity across several experimental tumor models. The term GVAX can connote GM‐CSF secreting cell vaccines prepared with different vectors as well as vector targets including autologous tumor cells, allogeneic tumor cell lines, and bystander third party tumor cells lines. GVAX has been evaluated against solid tumors, hematologic malignancies, and in the context of hematopoietic stem cell transplantation. GVAX has been extensively studied in clinical trials, both alone and in conjunction with lymphodepleting chemotherapy, immune checkpoint inhibitors, and other vaccines.